Development of the wave spectrum of the northern region of the Bay of Bengal based on Indian National Centre for Ocean Information Services (INCOIS) moored buoy data - Mansur, M.; Enam, F B; Baree, M S (Journal of Mechanical Engineering, 2018)
The wave spectrum of the northern region of the Bay of Bengal is developed and analyzed. A meticulous analysis shows variations of the wave spectrum of this region in the four meteorological seasons namely spring (March, April, May), summer (June, July, August), autumn (September, October, November) and winter (December, January, February). Real time wave data have been collected from a moored buoy of Indian National Centre for Ocean Information Service (INCOIS) located at 89.675° E longitude and 18.191° N latitude. Varying two-parameter (mean wave period and significant wave height) wave spectra for the four seasons are obtained and formulae for all the four spectra are derived. The adequacy of the different spectra is indicated by comparing with different wave spectra of known formulations.